2016
DOI: 10.1016/j.bbrc.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Core 2 β-1, 6-N-acetylglucosaminyltransferase-1 expression in prostate biopsy specimen is an indicator of prostate cancer aggressiveness

Abstract: Introduction: To avoid over-treatment of early stage prostate cancer (PCa), predictive biomarkers for PCa aggressiveness which can be obtained during pre-treatment evaluation are essential. Core 2 β-1, 6-N-acetylglucosaminyl-transferase-1 (GCNT1) is a key enzyme that forms core 2 branched O-glycans, the expression of which is associated with aggressive potential of prostate cancer. We examined whether GCNT1 expression in prostate biopsy specimen can predict cancer recurrence after radical prostatectomy for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Furthermore, O-glycan-terminated MUC1 reduces the adhesive characteristics of PCa cells [122]. When C2GnT-1-overexpressed PCa cells were injected into nude mice, it resulted in larger tumors compared to the vector control [123]. C2GnT1-expressing PCa cells possessed higher binding to prostate stromal cells and released significantly higher amounts of growth factors, such as HGF, FGF, and VEGFA.…”
Section: Mechanistic Insights Of C2gnt1/gcnt1 In Prostate Cancermentioning
confidence: 99%
“…Furthermore, O-glycan-terminated MUC1 reduces the adhesive characteristics of PCa cells [122]. When C2GnT-1-overexpressed PCa cells were injected into nude mice, it resulted in larger tumors compared to the vector control [123]. C2GnT1-expressing PCa cells possessed higher binding to prostate stromal cells and released significantly higher amounts of growth factors, such as HGF, FGF, and VEGFA.…”
Section: Mechanistic Insights Of C2gnt1/gcnt1 In Prostate Cancermentioning
confidence: 99%
“…Study has found that GAPDH itself or GAPDH-related proteins may be involved in lung tumorigenesis [28]. The expression of GCNT1 has strong correlation with tumorigenicity, development and metastasis in human prostate cancers [29, 30]. Furthermore, recent study has identified that DNA methylation of the SLC16A3 promoter is involved in the regulation of monocarboxylate transporter 4 (MCT4) in renal cancer resulting in cell apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Role in synthesising the F77 antigen which increases prostate cancer cell growth . Correlates with aggressive disease (Kojima et al 2015) and is a predictor of recurrence after radical prostatectomy (Sato et al 2016). Detected in patient urine (Kojima et al 2015).…”
Section: :3mentioning
confidence: 99%
“…Our analysis of the prostate cancer transcriptome also identified the core 2 branching enzyme GCNT1 as an AR target gene in prostate cancer patients . GCNT1 is upregulated in prostate cancer in which its expression correlates with aggressive disease and is a predictor of recurrence after radical prostatectomy (Hagisawa et al 2005, Kojima et al 2015, Sato et al 2016. GCNT1 can be detected in patient urine where in combination with PSA it is a reliable indicator for extracapsular extension of prostate cancer (Kojima et al 2015).…”
Section: :3mentioning
confidence: 99%